Interactive vocal communication at the nest by parent Great Tits Parus major. (5th May 2016) - Boucaud, Ingrid C. A.; Valère, Pénélope A.; Aguirre Smith, Mélissa L. N.; Doligez, Blandine; Cauchard, Laure; Rybak, Fanny; Vignal, Clémentine
Abstract : Although most bird species show monogamous pair bonds and bi‐parental care, little is known of how mated birds coordinate their activities. Whether or not partners communicate with each other to adjust their behaviour remains an open question. During incubation and the first days after hatching, one parent – generally the female – stays in the nest for extended periods, and might depend on acoustic communication to exchange information with its mate outside. The Great Tit Parus major is an interesting study system to investigate intra‐pair communication at the nest because males address songs to their mate while she is in the nest cavity, and females answer the male from the cavity with calls. However, the function of this communication remains unknown. In this study, we recorded the vocalizations and observed the resulting behaviour of Great Tit pairs around the nest at different breeding stages (laying, incubation and chick‐rearing). We observed vocal exchanges (vocalization bouts, alternated on the same tempo, between the female inside the nest and her male outside) in three contexts with different outcomes: (1) the female left the nest, (2) the male entered the box with food, and the female then used specific call types, (3) mates stopped calling but did not leave or enter the nest. The structure of vocal exchanges was globally stable between contexts, but females used calls with an up‐shifted spectrum during exchanges, at the end of which they left the nest or the male entered the nest. Birds vocalized more and at higher tempo during exchanges that ended up in feeding inside the nest. Birds also vocalized more during exchanges taking place during laying – a period of active mate guarding – than during incubation. We conclude that vocal exchanges could signal the females' need for food and the males' mate guarding behaviour, and discuss other possible functions of this communication.